Addition of Capecitabine to Adjuvant Chemotherapy May be the Most Effective Strategy for Patients With Early-Stage Triple-Negative Breast Cancer: A Network Meta-Analysis of 9 Randomized Controlled Trials - Li, Zhiyang; Zheng, Jiehua; Ji, Zeqi; Chen, Lingzhi; Wu, Jinyao; Zou, Juan; Liu, Yiyuan; Lin, Weixun; Cai, Jiehui; Chen, Yaokun; Chen, Yexi; Lu, Hai (Frontiers in Endocrinology, 2022)
Background and objective: Previous studies determined the therapeutic effects of capecitabine-based chemotherapy regimens on early-stage triple-negative breast cancer (TNBC); however, the optimal strategy of capecitabine-based chemotherapy remains uncertain. We conducted this network meta-analysis to address this issue. Methods: We systematically searched PubMed, Embase, and the Cochrane Registry of Controlled Trials (CENTRAL) for retrieving eligible studies published before September 2021. Two independent reviewers extracted information from eligible studies using pre-designed data extraction sheet. The primary outcome included disease-free survival, and the second outcome had overall survival and adverse events. Direct meta-analysis was performed using RevMan 5.4, and Bayesian network analysis was performed using R version 3.6.1 with the “gemtc” and “rjags” package. Results: Nine studies involving 3661 TNBC patients met the selection criteria. Network meta-analysis suggested that the addition of capecitabine to adjuvant chemotherapy achieved a significantly longer disease-free (HR=0.66, 95CrI=0.49 to 0.86) and overall survival time (HR=0.60, 95CrI=0.43 to 0.83) than standard chemotherapy. All comparisons did not achieve statistical significance. The addition of capecitabine to adjuvant chemotherapy was the most effective regime for improving disease-free (81.24%) and overall survival (78.46%) time, and the replacement of capecitabine to adjuvant chemotherapy was the safest regime. Conclusions: Based on available evidence, capecitabine-based chemotherapy benefits TNBC patients, and the addition of capecitabine to adjuvant chemotherapy was the most effective regime. In contrast, the replacement of capecitabine to adjuvant chemotherapy was the safest regime. More studies of high quality and large scale are needed to confirm our findings.